2009
DOI: 10.1590/s1678-77572009000700008
|View full text |Cite
|
Sign up to set email alerts
|

The Virtual Man Project's CD-ROM "Voice Assessment: Speech-Language Pathology and Audiology & Medicine", Vol.1

Abstract: The CD-ROM “Voice Assessment: Speech-Language Pathology and Audiology & Medicine” was developed as a teaching tool for people interested in the production of the spoken or sung human voice. Its content comprises several subjects concerning the anatomy and physiology of spoken and sung voice. A careful assessment becomes necessary in order to ensure the effectiveness of teaching and learning educational materials, whether related to education or health, within the proposal of education mediated by technology. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
6
0
2
Order By: Relevance
“…Other studies agree with this finding, demonstrating that students have considered several ICTs effective for the transmission of knowledge, because they make learning with interactive resources dynamic. 25 26 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies agree with this finding, demonstrating that students have considered several ICTs effective for the transmission of knowledge, because they make learning with interactive resources dynamic. 25 26 …”
Section: Discussionmentioning
confidence: 99%
“…The same happened with junior high and high school teachers via a distance learning course about vocal health and expressiveness (3) . Another interactive resource used was the CDROM Homem Virtual Voz (Virtual Man Voice), Volume 1, released by Speech and Language Pathology students, to instruct about anatomophysiology of the voice and speech, and about singing voice (4) . A virtual learning environment (ambiente virtual de aprendizagem, AVA (5) , in Portuguese) was developed with the intention to prepare undergraduate students of Speech and Language Pathology to carry out a perceptive-auditory assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the aforementioned results of the use of computer games in teaching and learning, studies have also shown that the integration of computer simulators (e.g., animations, visualizations, and interactive laboratories) in these contexts may provide students with opportunities to foster their comprehension of non-observable phenomena in science and make abstract concepts visible (8) . In Speech-Language and Hearing Sciences, recent work on Anatomy and Physiology has suggested that there has been a substantial increase in students' theoretical knowledge after the use of computer 3D models, and that such models seemed to be more effective in learning than the exclusive use of the traditional methods (9,10) . There are few but recent studies in this area; for this reason, more studies are necessary to confirm that learning using simulators is comparable to traditional learning (11) .…”
Section: Introductionmentioning
confidence: 99%